2020
DOI: 10.1021/acsapm.0c00760
|View full text |Cite
|
Sign up to set email alerts
|

Design of Self-Cross-Linkable Poly(n-butyl acrylate)-co-poly[N-(hydroxymethyl)acrylamide] Amphiphilic Copolymers toward Elastic and Self-Healing Properties

Abstract: A huge challenge for developing self-healing materials is achieving a good compromisation between mechanical properties and self-healing efficiency. For this purpose, a facile route by introducing N-(hydroxymethyl)­acrylamide (NMA) as a thermal-catalyzed self-cross-linker as well as a self-healing material into a soft polymer system for tuning the mechanical properties in an easy way, resulting in elastic and self-healing properties through a covalent and dynamic network simultaneously, represents an exciting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…After 6 h cross-linking, the −OH peaks of the copolymer and the 1.5 wt % nanocomposite are red-shifted to 3350 and 3355 cm –1 , respectively, together with a decrease in the characteristic peak intensities, indicating the loss of the OH group in the polymer chain. Such changes of signals confirm the breakage of the OH bond and the formation of a covalent bond during the cross-linking reaction . On the contrary, all of the amine (−NH and C–N), carbonyl (CO), and carboxyl (−COOH)) groups of the 6c-1.5 wt % nanocomposite film were shifted, implying that the introduction NGQDs into the polymeric network not only enhances the covalent bonding but also triggers the improvement of non-covalent interactions in the nanocomposite system (Figure S4b).…”
Section: Results and Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…After 6 h cross-linking, the −OH peaks of the copolymer and the 1.5 wt % nanocomposite are red-shifted to 3350 and 3355 cm –1 , respectively, together with a decrease in the characteristic peak intensities, indicating the loss of the OH group in the polymer chain. Such changes of signals confirm the breakage of the OH bond and the formation of a covalent bond during the cross-linking reaction . On the contrary, all of the amine (−NH and C–N), carbonyl (CO), and carboxyl (−COOH)) groups of the 6c-1.5 wt % nanocomposite film were shifted, implying that the introduction NGQDs into the polymeric network not only enhances the covalent bonding but also triggers the improvement of non-covalent interactions in the nanocomposite system (Figure S4b).…”
Section: Results and Discussionmentioning
confidence: 87%
“…Adjustable Mechanical Properties of the Nanocomposite Films. Following our previous study, the reported PBA x -co-PNMA y synthesized using the ATRP method 25 ( 1 H NMR, GPC, and FTIR profiles are included in Figures S3 and S4) was combined with NGQDs via simple blending as illustrated in Figure 1 (see the Experimental Section/Methods for details). The aim of the experimental strategy is the construction of hydrogen bonds between the functional groups of NGQDs and the side chains of the NMA-segment in a copolymer, enacting as the main cross-linking site in the nanocomposite system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations